Analisis Laju Korosi Baja AISI 1040 Pada Bagian Daun Kemudi Perahu Nelayan Tradisional: Pendahuluan, - Ahmad Pauzi; Agus Fikri; Delvis Agusman; Mohammad Mujirudin; Arry Avorizano (Universitas Muhammadiyah PROF. DR. HAMKA Fakultas Teknik – Program Studi Teknik Mesin, 2026)
Abstract The ship's part that plays an important role in controlling the direction of the ship is the rudder, where the rudder has a shaft and rudder blade. The significant threat of corrosion encourages the development of various ways to protect against potential damage. In order to extend the service life of the product, it is necessary to choose the right material and coating. The purpose of this study was to determine the corrosion rate of AISI 1040 steel material with paint, chrome and uncoated coatings with varying immersion times using experimental methods. After corrosion testing, it was found that uncoated steel had the highest corrosion rate of 16.0343 mmpy, the highest corrosion rate with coating in steel occurred in the paint coating of 0.7792 mmpy, while the lowest corrosion rate occurred in steel with chrome coating of 0.1716 mmpy. Based on the results of this study, it can be seen that AISI 1040 steel must be coated in order to reduce the rate of corrosion that occurs. The corrosion that occurs in uncoated steel specimens is uniform corrosion, and with paint and chrome coatings is pitting corrosion. Keywords: rudder, corrosion rate, chrome plating